Resiliency for Independent Living of Veterans with Disabilities - Lakshini Ruchiranga Abeywickrama; H. M. S. Niroshani (Asian Social Work Journal, 2021)
This paper reports on a thematic analysis focusing on the perspective of veterans regarding social pressure experienced after the disability. The veterans returned from the battlefield, disabled, resented, and traumatized. They were eventually required to adopt with unanticipated lifestyle changes. This had life-long effects on the veterans along with the struggle of coping with societal demands. In this milieu, this study aims to identify the external constraints experienced by veterans with disabilities to lead independent lives. In addition, the focus on the existing resilience among veterans also is specified in the study. To garner information, ten in-depth interviews are conducted with selected male veterans in a rehabilitation center in Sri Lanka. The study identified unhealthy relationship patterns developed between veterans and their intimate family members as one of the constraints for veterans to lead an independent life. Changes in roles and responsibilities within the family, lack of attention from the partner, infidelity, lack of emotional attachment with children are identified as type of disruptive relationship patterns experienced by veterans after their disability. Lack of social acceptance on the other hand lessen the scope of veterans with disabilities to carry out independent lives. Labelling, exclusion from community activities, unrealistic demands to perform life tasks as exactly as before are recognized as data related to decreased social acceptance. Lifestyle changes in terms of having to adopt to a daily schedule, limited access to realize personal preferences are perceived as challenges to lead independent lives. Lack of self-esteem among veterans with disabilities has diminished their potential to bounce back from the adversity. The need of augmenting resilience skills of veterans with disabilities is therefore recommended in this study.